Digital engineering with Minecraft - Kelly, James F. (James Floyd) (Que, 2016)
Minecraft is a global phenomenon and obsession: millions of kids and adults are passionately involved in building and exploring their own Minecraft worlds. Now they can master valuable real-world Computer-Aided Design (CAD) career skills while they're having fun with Minecraft. Digital Engineering with Minecraft teaches simple, hands-on CAD techniques that are directly useful in Minecraft and easily transferable to more advanced tasks and software. Through hands-on projects, James Floyd Kelly introduces Minecraft players to seven specialized tools and applications for taking their Minecraft worlds to a whole new level. Purchasers of this book also get free access to hands-on how-to videos guiding you through many key tasks. Kelly's detailed walkthroughs guide you through every step of designing objects in CAD, 3D printing, game programming, animation, and more. You'll discover how to take what you've learned and created outside Minecraft and pull it directly into your Minecraft world. Coverage includes: Finding great objects on Thingiverse and importing them to Minecraft with MCeditUsing basic tools including maze makers and the Online-Convert toolMastering key Tinkercad skills, including shape creation, rotation, resizing, and groupingCreating and exporting monsters with 123D Creature for iPadPutting yourself in the game with 123D Catch for PC, Mac, or iPadUsing 123D Sculpt to create incredible new landscapesCreating hollow wire-frame domes that transform any terrain into a battle arenaGenerating unique items with ShapeshifterDigital Engineering with Minecraft will help you transform all of your worlds - both inside and outside Minecraft!